Analisis SWOT Upaya Pengembangan Bisnis Kuliner Pasar Ramadan (Study kasus pada UMKM Pasar Ramadan Food kota Palangka Raya) - Lotmidayanti Berutu; Risda Oktavia Siahaan; Muhammad Farras Nasrida (Pusat Riset dan Inovasi Nasional, 2023)
Pasar Ramadhan is an MSME business that sells various kinds of culinary or snacks that are very popular with the community. Food and drinks are sold such as fried meatballs, chips, cakes, boba, lemon tea, chicken noodles, grilled chicken, satay, and so on. This journal article was created to discuss SWOT analysis in an effort to develop a culinary business in the Ramadan market. This study aims to identify internal and external factors that influence culinary business development in the Ramadan market and provide recommendations for appropriate business development strategies. The research method used is descriptive analysis by collecting data through interviews with traders and visitors to the Ramadan market as well as through literature study. The results of the study show that internal factors such as product quality, price and promotion influence the culinary business development in the Ramadan market, while external factors such as market conditions, competition and regulations also play an important role in the culinary business development in the Ramadan market. Recommendations for the right business development strategy include improving product quality, price adjustments, and increasing promotions to increase the attractiveness of the culinary business in the Ramadan market. In addition, traders are also advised to pay attention to market conditions and existing competition and comply with applicable regulations to optimize culinary business development in the Ramadan market.